Testing Convergence of Fiscal Policies in Regions of Turkiye - Karaş, Göksel; Karas, Ebru (Ekonomika, 2023)
The presence of convergence in the fiscal policies implemented at the national level in order to eliminate regional inequalities is an indication that the resources are rationally distributed among the regions and the differences are decreasing. From this point of view, in this study, it is aimed to investigate the convergence of the fiscal policy implemented in the period of 2004:01-2020:12 in Turkey within the scope of the fiscal purpose of taxes. In the study, nonlinear convergence analysis was performed, but linear convergence analysis was used because the linearity hypothesis could not be rejected. According to the findings, there is an absolute convergence between the regions in the fiscal policy implemented in Turkey. However, in terms of regions, the first region is differentiated from other five regions, while the other regions are very close to each other. Regarding this, it may be possible to bring the first region and the other five regions closer to each other by reducing the difference with the arrangements to be made in taxation policies. The obtained findings offer important implications for policy makers.